Variations in Satisfaction from Prepaid and Postpaid Electricity Use Based on Community Perception in Bandar Sribhawono - Sandora, Putri; Sugiono, Sugiono; Saputra, Ardian (Utan Kayu Publishing, 2024)
During World War II, electricity companies in Indonesia were controlled by Japan and subsequently seized by Indonesian youths after independence in September 1945, then handed over to the Republic of Indonesia government. President Sukarno established the Electricity and Gas Office on October 27, 1945. PLN (State Electricity Company) has adopted various innovations, including Prepaid Electricity Service (LPB), as part of efforts to enhance service quality to the public.This study focuses on comparing satisfaction between Prepaid and Postpaid electricity users based on community perceptions in Bandar Sribhawono. Data analysis methods using Chi-Square test and Coefficient of Contingency indicate that the presence of Prepaid PLN significantly contributes to improving community satisfaction, with a contingency coefficient value of 0.7985, exceeding the critical value set.These findings suggest that promotional strategies and services implemented by PT PLN (State Electricity Company) Distribution in Bandar Sribhawono have the potential to influence public preferences in choosing between Prepaid and Postpaid electricity. The implications of these findings can serve as a basis for enhancing marketing strategies and services to achieve broader adoption of Prepaid Electricity in the future.